The Effects of Nigeria's Membership of the World Trade Organization (WTO) on the Textile Industry in Nigeria - Udeoji, Ebele Angela (2015)
This study examined the political and economic factors that influenced the Nigerian membership of the World Trade Organization (WTO) and the effects of the membership on the textiles industry since 1995. It also identified the problems of the industry and their linkages to its membership of the world body with a view to ascertaining whether or not its membership is benefiting maximally.